A Systematic Literature Review on Consumer Behaviour in Innovative Last-Mile Delivery - Fara Adura, Mohd Yusoff; Fazeeda, Mohamad; Puteri Fadzline, Muhamad Tamyez; Siti Aisyah, Panatik (GBMR, 2023)
Purpose: The main purpose of this paper is to determine the current trend of study in innovative last-mile delivery and the factors that influence consumers’ behaviour in innovative last-mile delivery. Design/methodology/approach: This systematic literature review is guided by established guidelines and covers six important steps in the methodology: verification of established guidelines, creation of research questions, searching strategy (the process of identification, screening and eligibility) on a few reputable databases such as Scopus, Web of Science and also Google Scholar, continued with data appraisal, data extraction and data analysis. Research articles between 2017 and 2021 were gathered based on the selected keywords and inclusion criteria. Findings: The findings revealed that most of the studies emphasised the antecedents of the initial use of innovative last-mile delivery. Intention emerged as the main dependent variable in many studies, followed by preferences, attitudes, and other variables. Meanwhile, the significant independent variable is from different factors such as technical factors, socio-economic factors, delivery factors, and others. In terms of the theory, the theory of planned behaviour was widely used in the selected studies compared to other theories.Research limitation/implication: Through a rigorous systematic literature review, this study depicts the gaps in the studies of consumer behaviour toward innovative last-mile delivery. Practical Implications: This study contributes to a deeper understanding of consumers’ behavioural towards innovative last-mile delivery. The findings of this study are valuable not only to scholars but also to logistics practitioners and policymakers. This study could help guide the company and related agencies in increasing the intention and adoption of innovative last-mile delivery and successfully implementing new last-mile delivery solutions. Originality/value: To the best of author’s knowledge, little effort has been devoted to systematising the literature on consumer behavioral toward innovative last-mile delivery. This research helps to close this gap.